First dynamics of bacterial community during development of Acropora humilis larvae in aquaculture - Chitrasak Kullapanich (Nature Portfolio, 2021)
Abstract A symbiosis of bacterial community (sometimes called microbiota) play essential roles in developmental life cycle and health of coral, starting since a larva. For examples, coral bacterial holobionts function nitrogen fixation, carbon supply, sulfur cycling and antibiotic production. Yet, a study of the dynamic of bacteria associated coral larvae development is complicated owning to a vast diversity and culturable difficulty of bacteria; hence this type of study remains unexplored for Acropora humilis larvae in Thai sea. This study represented the first to utilize 16S rRNA gene sequencing to describe the timely bacterial compositions during successfully cultured and reared A. humilis larval transformation in aquaculture (gametes were collected from Sattahip Bay, Chonburi province, Thailand), from gamete spawning (0 h) and fertilization stage (1 h), to embryonic cleavage (8 h), round cell development (28, 39 and 41 h), and planula formation (48 h). The sequencing results as estimated by Good’s coverage at genus level covered 99.65 ± 0.24% of total bacteria. While core phyla of bacteria were observed (Proteobacteria, Actinobacteria, Firmicutes and Bacteroidetes), changes in bacterial population structures and differential predominant core bacterial orders were denoted for each larval developmental stage, from fertilization to embryonic cleavage and subsequently from the embryonic cleavage to round cell development (P = 0.007). For instances, Pseudoalteromonas and Oceanospirillales were found prevalent at 8 h, and Rhizobiales were at 48 h. The bacterial population structures from the round cell stage, particularly at 41 h, showed gradual drift towards those of the planula formation stage, suggesting microbial selection. Overall, this study provides preliminary insights into the dynamics of bacterial community and their potentially functional association (estimated from the bacterial compositions) during the developmental embryonic A. humilis in a cultivation system in Southeast Asia region.